Systematic Review on the Implementation of Photovoltaic Systems in Rural Areas Without Electrical Services in Latin America - Carpio Terrazos, Flavio Luis Celinny; Choque Yarasca, Christel Lucero; Castillo Siguas, Esther Oriele; Gimenez Lopez, Bruno; Godoy Laurente, Lucy Veronica (LACCEI, 2025)
Abstract- The study aims to examine the impact of photovoltaic systems in rural areas without access to electricity in Latin America, identifying best practices, lessons learned and opportunities for future research. This will provide a basis for informed decisions and effective policies to promote sustainable development in the region. A systematic literature review was conducted using the PICOC strategy to formulate questions on quality of life, environmental impact, economic benefits and sustainable development. Databases such as Scopus were used and rigorous inclusion and exclusion criteria were applied. The selection process followed the PRISMA methodology to ensure completeness and objectivity. The results showed that between 2020 and 2024 more studies on photovoltaic systems were published. Brazil is the leading country in terms of number of studies, followed by Colombia, Bolivia, Ecuador, Argentina, Mexico and Peru. The results show that solar energy has made it possible to expand energy coverage, reduce carbon emissions and foster economic development by boosting agricultural, commercial and tourism activities. Furthermore, it was identified that, although the initial investment in solar panels remains an obstacle, the operational and maintenance costs are significantly lower in the long term. However, the literature reviewed highlights the need for affordable financing strategies, recycling programmes for solar components and technical training to ensure the sustainability of these systems. In conclusion, PV represents a viable solution for rural electrification, but its long-term success will depend on policy.